Clinical outcomes of tibial nonunion treatment through the combination of PRP, autogenous iliac bone grafting, and augmentation plating - Lu, Guoliang; Huo, Zhiqian; Chen, Enliang (Frontiers in Surgery, 2025)
ObjectiveTo explore the clinical efficacy of PRP (Platelet-Rich Plasma), autogenous bone combined with augmentation plating in the treatment of tibial nonunion.MethodsA total of 45 patients with tibial nonunion who fulfilled the inclusion criteria were meticulously selected and subsequently randomized into three distinct groups: Group A, which received PRP, autogenous bone grafting, and augmentation plating; Group B, which underwent autogenous bone grafting and augmentation plating; and Group C, which only received autogenous bone grafting. Each group comprised 15 patients. Detailed records were maintained for gender, age, BMI (Body Mass Index) as general information, surgery duration, blood loss, length of hospital stay, fracture healing time, and the Fernadez-Esteve score at three specific time points.ResultsNo statistically significant differences were observed in the general demographic data, including gender, age, and BMI, among the three groups (P > 0.05). In terms of bone healing time, Group A exhibited the shortest duration, followed closely by Group B and then Group C. Additionally, Group A demonstrated significantly higher Fernadez-Esteve scores compared to Group B, with Group C trailing behind, at 3, 6, and 9 months postoperatively.ConclusionPRP, autogenous bone combined with augmentation plating in the treatment of tibial nonunion can promote fracture healing and repair, improve fracture healing rate, and the clinical effect is significant.